Analysis of predictors of sick sinus syndrome after open surgical treatment of atrial fibrillation - Vadim A. Karnakhin (Concilium Medicum, 2021)
Aim. To identify and analyze predictors of the development of sick sinus syndrome in patients with atrial fibrillation.